Temperatue. - Rodgers, Alan. (Chicago Heinemann Library, 2003)
Provides an introduction to temperature, examining how it is measured and the relationship between temperature and weather.
1 - 6
Keywords: Atmospheric temperature; Weather; Measuring the Weather